Entri, Makna dan Padanan dalam Kamus Dwibahasa Melayu-Inggeris: Satu Analisis Semantik Ranahan (Jurnal Bahasa, 2012)
This article discusses the sense division of the entry "menjulang" in two Malay-English bilingual dictionaries: Intelek Malay- Bahasa Dictionary and Kamus Perwira Bahasa Melayu-Bahasa Inggeris. A questionnaire study showed that "menjulang" is the most problematic entry due to its incomplete coverage in terms of meaning and equivalent. The Frame Semantics theory is chosen as the basis for analysis based on data from the five million-words UKM-DBP Malay corpus. Linguistic analysis is not only based on corpus data but also on the Malay and English monolingual dictionaries, while English equivalents are taken from the FrameNet database. Frame Semantics analysis organises sense divisions based on frame elements and word valency. This article also proposes a better organised entry for "menjulang" together with its English equivalents.Keywords: bilingual dictionaries, Frame Semantics, sense, valency, FrameNet